Postburn head and neck reconstruction using tissue expanders - Fattah, Jalal Hamasalih (Zanco Journal of Medical Sciences (ZJMS), 2014)
Background and objective: Tissue expanders are useful adjuvant in reconstruction after burn. The technique provides tissue of similar texture and color to the defect to be covered and has the added advantage of minimal donor site morbidity. The study aimed to assess the outcome and complications of using tissue expansion for head and neck postburn reconstruction. Methods: Thirty patients with head and neck burn scar, treated with thirty eight tissue expanders, were included in this prospective study at the Plastic Surgery Department in Rizgari Teaching Hospital in Erbil from April 2009 to November 2012, with the mean age of 14 years. Statistical package for social sciences (SPSS version 18) was used for data entry and analysis. Results: The commonest use of tissue expander was for treating postburn scar alopecia (18 patients, 60%), followed by postburn cheek scar (six patients 20%). The scar size ranged from 4x10cm to 16x24cm. Complete burn scar excision was possible in 80% of cases with single or multiple sessions of expansion. Early exposure of the expander followed by infection occurred in three cases (10%), which led to interruption of the expansion and expander removal. Satisfactory results were achieved after reconstruction in 90% of cases. Conclusion: Tissue expansion, if carefully planned and conducted, is one of the treatments of choice for post-burn reconstruction of the head and neck, allowing an expanded flap suitable for versatile coverage.